Pengaruh Stres Kerja dan Perilaku Cyberloafing terhadap Kinerja Karyawan: (Effect of Work Stress and Cyberloafing Behavior on Employee Performance) - Alfina Damayanti; Keumala Hayati; Nova Mardiana (UPT Penerbitan Universitas Jember, 2022)
This study aims to determine the effect of work stress and cyberloafing behavior on the performance of employees. This study uses primary data from the results of a questionnaire with a Likert scale. The object of this research is the employees of PT. Inbio Tani Nusantara. Sampling used the saturated sampling method (census), where all population members were used as samples of 139. The data analysis used was multiple linear regression analysis with SPSS 25 as an analytical tool. The results showed that work stress had a significant positive effect on employee performance, and cyberloafing behavior significantly negatively affected employee performance. The limitation of this research is that the object of research is only limited to one company, namely employees of PT. Inbio Tani Nusantara and the sample used is relatively small. This study's results are related to work stress and cyberloafing behavior.